Analysis of total suspended solids in Sungai Maong Kiri - Mohamed Yaacob, Y.A (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study is about suspended solids analysis in Sungai Maong Kiri. This area is chosen because it has high population density. This analysis is to observe changing of trend experienced by suspended solids. High suspended solids content in water would result river to become cloudy and polluted. The suspended solid main source is from erosion because of development and also from man-made pollution, discharge waste water into the river. Apart from that, this study also tries to simulate water quality model by using suspended solids parameter. That simulation will use 'Water Analysis Simulation Programme 7 (WASP7) software. Besides WASP7 software, this analysis could also be done by using 'Microsoft Excel'. At the same time, this study is also to compare the suspended solids trend with the standard value. From comparison, river classification can be determined. Based from the result, it is found in certain years that suspended solids in Sungai Maong’s upstream are higher than the downstream of the river. Suspended solids’ concentration values are high during early and end of the year while lowest concentration value is recorded in the middle of the year. This scenario probably is affected by the rain. Rain will cause the land to be eroded and rain will carry the sediment into the river. As a conclusion, Sungai Maong is classified as 11B class and unpolluted in term of total suspended solids.